1978
DOI: 10.1210/jcem-47-5-1042
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cushing's Syndrome with Trilostane (WIN 24,540), an Inhibitor of Adrenal Steroid Biosynthesis*

Abstract: Seven patients with Cushing's syndrome were treated with trilostane (WIN 24,540) 4 alpha,5-epoxy-17 beta-hydroxy-3-oxo-5 alpha-androstane-2 alpha-carbonitrile), an inhibitor of adrenal steroid biosynthesis. Trilostane treatment reduced steroid biosynthesis and it also improved biochemical manifestations of the disease in all of the patients treated. The average cortisol secretory rate decreased significantly with treatment, from 47.1 to 23.4 mg/24 h (P less than 0.005), and urinary 17-hydroxycorticosteroids de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(58 citation statements)
references
References 33 publications
(32 reference statements)
2
56
0
Order By: Relevance
“…Trilostane has been used successfully in conditions associated with overproduction of adrenal steroids, such as Cushing's and Conn's syndromes. 12,13 In breast cancer, several trials showed that trilostane at doses up to 960 mg/day (with hydrocortisone or other glucocorticoid supplement to compensate for adrenal inhibition) was indeed effective as a therapy for the control of post-menopausal breast cancer. 14 -20 However, when all the trials, totalling nearly 800 patients, are taken into account, there appear to be anomalies not accounted for by the postulated mode of action.…”
mentioning
confidence: 99%
“…Trilostane has been used successfully in conditions associated with overproduction of adrenal steroids, such as Cushing's and Conn's syndromes. 12,13 In breast cancer, several trials showed that trilostane at doses up to 960 mg/day (with hydrocortisone or other glucocorticoid supplement to compensate for adrenal inhibition) was indeed effective as a therapy for the control of post-menopausal breast cancer. 14 -20 However, when all the trials, totalling nearly 800 patients, are taken into account, there appear to be anomalies not accounted for by the postulated mode of action.…”
mentioning
confidence: 99%
“…63 The initial results were enthusiastic, 64 but more recently trilostane has been found to be relatively ineffective in Cushing's syndrome. 65 Ketoconazole, an imidazole derivative with antifungal properties, has been shown to block adrenocorticosteroid synthesis and blunt ACTH-induced cortisol release.…”
Section: Therapymentioning
confidence: 99%
“…Here we report a patient with Cushing's syndrome due to AIMAH who was treated for 7 years with trilostane, which inhibits the synthesis of cortisol by competitive and reversible blocking of 3β-hydroxysteroid dehydrogenase (3β-HSD) (5). This case may suggest a possible new approach to the management of Cushing's syndrome due to AIMAH.…”
Section: Introductionmentioning
confidence: 97%